ANALISIS KEBIJAKAN PENANGGULANGAN KEMISKINAN MELALUI PENDIDIKAN BOARDING SCHOOL SMK NEGERI 3 DI KABUPATEN PURBALINGGA - Sabani, Ivana Andi; ., Sulistyowati; Adnan, Muhammad (Journal of Politic and Government Studies, 2017)
Poverty is a classic problem of mankind in every part of the world and becomes a complex issue because it is not just about low income. The low level of education, skills, and the lack of introduction to technology are the human resource constraints that are closely related to the causes of poverty. Purbalingga regency is one of the areas with a high percentage of poor people who are always ranked in the poorest areas in Central Java Province. The purpose of this research is to analyze the policy of poverty reduction by Purbalingga Government through establishment of Boarding School of SMK Negeri 3 Purbalingga.This study uses mixed methods between qualitative and quantitative with a qualitative approach remains the main approach. Data collection techniques were carried out, among others, by collecting documents and in-depth interviews with actors involved in the policy, and using a research questionnaire to the research subjects of alumni / boarding school graduate SMK Negeri 3 Purbalingga. Analysis of research data is done by combining primary data obtained and findings in both qualitative and quantitative data.Based on the research that has been done, it is known that the policy has been implemented optimally, consistently, and there is a continuous suitability of vision among policy actors in 3 different Heads of District (Bupati), and achievements that can penetrate TOP 35 in Public Service Innovation Competition (SiNovik) 2016. Quantitative data shows that there is an increase of living standards of alumni SMK Negeri 3 Purbalingga coming from poor families, as the object of poverty problem in Purbalingga Regency. This shows that policies that have the principle of breaking the poverty chain have succeeded in reducing the number of poor people, the sustainability of the program is likely to reduce poverty significantly.Keywords: Poverty Reduction, Education Implementation Model, Policy Implementation.